Peranan Kemasan Pada Hasil Tanaman Industri - Zein Nasution; Wakhjuddin Ciptadi (Balai Besar Kimia dan Kemasan, 1978)
From technical point of view the packaging function are 1) to keep the product in a good condition during distribution and storage, 2) to protect the product from the mechanical destruction, 3) to protect the product from contamination, oxidation macro/micro organism, light, and humidity, 4) to keep the environment so that product can be stored much longer. Whereas from comercial view point the packaging function are ; 1) to make the product more attractive, 2) to mini mize the possibility of lossing, and 3) to give information of the product· such as specification, price, and weight. There are many packaging material can be used for industrial crops. It is caused by wide variety of the crops and also theform and material of packaging must fulfill a certain requirement.